Proposed use of the international classification of functioning, disability and health to evaluate quality of life after an amputation - Andersom Ricardo Fréz; Amirah Ali Abdallah; Christiane Riedi; Janaine Galindo; João Afonso Ruaro; Simone de Carvalho Ribeiro
Objective To quantify the quality of life of people with a lower limb amputation, and to propose a relationship between the quality of life and the International Classification of Functioning, Disability and Health (ICF). Materials and methods After a retrospective study of medical records, 15 amputees met the inclusion criteria. The characteristics of the amputation and quality of life were evaluated, and both were correlated with the ICF. The 36-Item Short-Form Survey (SF-36) was used to assess quality of life. Results It was possible to establish ICF codes for levels of amputation and the quality of life. A high and significant correlation was found between quantitative descriptors of the ICF and SF-36 scores (r = -0.9376, p < 0.0001). Conclusion People with a lower limb amputation showed a reduced quality of life, which was reflected in scores from a generic questionnaire and their correlation with the ICF.